Yugoslav survey (Jugoslavija Pub. House, 1960)
With an offprint of Vladimir Cvetkovic's study "Yugoslavia's share in international trade in basic commodities".Continued by: Pregled, Srbija i Crna Gora. English. Survey, Serbia & Montenegro, ISSN 1451-477X.